Phillyrin prevents sepsis-induced acute lung injury through inhibiting the NLRP3/caspase-1/GSDMD-dependent pyroptosis signaling pathway - Ji Chen; Hao Xiaoyan; Li Zhiyi; Liu Jiaxing; Yan Hanyu; Ma Ketao; Li Ling; Zhang Liang (Acta Biochimica et Biophysica Sinica)
Acute lung injury (ALI) is a severe pulmonary disorder of sepsis with high clinical incidence and mortality. Nucleotide-binding oligomerization domain-like receptor family pyrin domain containing 3 (NLRP3)-cysteinyl aspartate specific proteinase 1-gasdermin D (GSDMD)-dependent pyroptosis of alveolar epithelial cells (AECs) has emerged as a crucial contributor to ALI during sepsis. Phillyrin (PHI), a natural lignan isolated from the traditional Chinese herbal medicine Forsythia suspensa, has been shown to have anti-inflammatory, antioxidant and antiviral properties. However, little is known about the protective role and potential mechanism of PHI in sepsis-induced ALI, and it is uncertain whether the protective effect of PHI in sepsis-induced ALI is connected to pyroptosis. This study aims to examine the preventive effects of PHI on sepsis-induced ALI via the inhibition of NLRP3/caspase-1/GSDMD-mediated pyroptosis in AECs. Our findings demonstrate that preadministration of PHI successfully reduces sepsis-induced pulmonary edema, systemic/pulmonary inflammation, and pulmonary histological damage in lung tissues, bronchoalveolar lavage fluid, and the serum of septic mice. Intriguingly, PHI preadministration suppresses sepsis-induced protein expressions of pyroptosis-specific markers, especially their active forms. In vitro assays show that PHI pretreatment also protects type II AECs (MLE-12) from lipopolysaccharide-induced pyroptosis by preventing the activation of the pyroptosis signaling pathway. The results from molecular docking and surface plasmon resonance reveal that PHI has a significant affinity for direct binding to the GSDMD protein, suggesting that GSDMD is a potential pharmacological target for PHI. In conclusion, PHI can prevent sepsis-triggered ALI by effectively suppressing the activation of the canonical pyroptosis signaling pathway and pyroptosis of AECs.